The Interpretive-Sensory Access Theory of Self-Knowledge: Simplicity and Coherence with Surrounding Theories - Rimkevičius, Paulius (Problemos, 2019)
The interpretive-sensory access (ISA) theory of self-knowledge claims that one knows one’s own mind by turning one’s capacity to know other minds onto oneself. Previously, researchers mostly debated whether the theory receives the most support from the results of empirical research. They have given much less attention to the question whether the theory is the simplest of the available alternatives. I argue that the question of simplicity should be considered in light of the well-established theories surrounding the ISA theory. I claim that the ISA theory then proves to be the simplest. I reply to objections to this claim related to recent developments in this area of research: the emergence of a unified transparency theory of self-knowledge and the relative establishment of the predictive processing theory.